1 | // $Source$ |
---|
2 | // $Revision: 2044 $ |
---|
3 | // $Date: 2006-08-01 17:31:01 +0000 (Tue, 01 Aug 2006) $ |
---|
4 | |
---|
5 | $use Apply Access Arithm Compare; |
---|
6 | |
---|
7 | $func Deparen-Term term = expr; |
---|
8 | Deparen-Term { |
---|
9 | (expr) = expr; |
---|
10 | term = term; |
---|
11 | }; |
---|
12 | |
---|
13 | $func Paren-Term term = (term); |
---|
14 | Paren-Term term = (term); |
---|
15 | |
---|
16 | Zip (e.list1) (e.list2) = |
---|
17 | (e.list1) (e.list2) /*empty*/ $iter { |
---|
18 | e.list1 : t.first1 e.rest1, |
---|
19 | e.list2 : t.first2 e.rest2 = |
---|
20 | (e.rest1) (e.rest2) e.new-list (t.first1 t.first2); |
---|
21 | } :: (e.list1) (e.list2) e.new-list, |
---|
22 | e.list1 : /*empty*/ = |
---|
23 | e.new-list; |
---|
24 | |
---|
25 | Map s.Fname e.Fargs (e.list) = |
---|
26 | () e.list $iter { |
---|
27 | e.list : t.item e.rest = |
---|
28 | (e.new-list <Apply s.Fname e.Fargs t.item>) e.rest; |
---|
29 | } :: (e.new-list) e.list, |
---|
30 | e.list : /*empty*/ = |
---|
31 | e.new-list; |
---|
32 | |
---|
33 | Filter s.Fname e.Fargs (e.list) = |
---|
34 | () e.list $iter { |
---|
35 | e.list : t.item e.rest, { |
---|
36 | <Apply s.Fname e.Fargs t.item> : e = |
---|
37 | (e.new-list t.item) e.rest; |
---|
38 | (e.new-list) e.rest; |
---|
39 | }; |
---|
40 | } :: (e.new-list) e.list, |
---|
41 | e.list : /*empty*/ = |
---|
42 | e.new-list; |
---|
43 | |
---|
44 | Split s.Fname e.Fargs (e.list) = |
---|
45 | () () e.list $iter { |
---|
46 | e.list : t.item e.rest, { |
---|
47 | <Apply s.Fname e.Fargs t.item> : e = |
---|
48 | (e.true-list t.item) (e.false-list) e.rest; |
---|
49 | (e.true-list) (e.false-list t.item) e.rest; |
---|
50 | }; |
---|
51 | } :: (e.true-list) (e.false-list) e.list, |
---|
52 | e.list : /*empty*/ = |
---|
53 | (e.true-list) (e.false-list); |
---|
54 | |
---|
55 | Elem? e.list t.item = |
---|
56 | e.list : e t.item e; |
---|
57 | |
---|
58 | Get-Elem s.num (e.list) = <L s.num e.list>; |
---|
59 | |
---|
60 | Foldr s.Fname e.Fargs (e.value) (e.list) = |
---|
61 | (e.value) e.list $iter { |
---|
62 | e.list : e.something t.last = |
---|
63 | (<Apply s.Fname e.Fargs t.last e.value>) e.something; |
---|
64 | } :: (e.value) e.list, |
---|
65 | e.list : /*empty*/ = |
---|
66 | e.value; |
---|
67 | |
---|
68 | Foldr1 s.Fname e.Fargs (e.list), { |
---|
69 | e.list : e.something t.last = |
---|
70 | <Foldr s.Fname e.Fargs (t.last) (e.something)>; |
---|
71 | /*empty*/; |
---|
72 | }; |
---|
73 | |
---|
74 | Concat e.lists = <Map &Deparen-Term (e.lists)>; |
---|
75 | |
---|
76 | Paren expr = <Map &Paren-Term (expr)>; |
---|
77 | |
---|
78 | Reverse { |
---|
79 | term e.list = <Reverse e.list> term; |
---|
80 | /*empty*/ = /*empty*/; |
---|
81 | }; |
---|
82 | |
---|
83 | Intersperse { |
---|
84 | (e.sep) /*empty*/ = /*empty*/; |
---|
85 | (e.sep) t1 = t1; |
---|
86 | (e.sep) t1 e.list = |
---|
87 | (t1 e.sep) e.list $iter { |
---|
88 | e.list : t2 e.rest = |
---|
89 | (e.new-list t2 e.sep) e.rest; |
---|
90 | } :: (e.new-list) e.list, |
---|
91 | e.list : t2 = |
---|
92 | e.new-list t2; |
---|
93 | }; |
---|
94 | |
---|
95 | Nub e.expr = |
---|
96 | e.expr () $iter { |
---|
97 | e.expr : term e.rest, { |
---|
98 | e.selected : e term e = e.rest (e.selected); |
---|
99 | e.rest (e.selected term); |
---|
100 | }; |
---|
101 | } :: e.expr (e.selected), |
---|
102 | e.expr : /*empty*/ = |
---|
103 | e.selected; |
---|
104 | |
---|
105 | Replicate s.n e.expr = |
---|
106 | s.n /*e.list*/ $iter |
---|
107 | <"-" s.n 1> e.list e.expr |
---|
108 | :: s.n e.list, |
---|
109 | <"<=" (s.n) (0)> = |
---|
110 | e.list; |
---|
111 | |
---|
112 | /* |
---|
113 | * Returns number of e.expr entries in e.source and e.source without all e.expr's. |
---|
114 | */ |
---|
115 | Entries e.expr (e.source) = |
---|
116 | 0 e.source () $iter { |
---|
117 | e.source : e1 e.expr e2 = <"+" s.num 1> e2 (e.res e1); |
---|
118 | s.num (e.res e.source); |
---|
119 | } :: s.num e.source (e.res), |
---|
120 | e.source : /*empty*/ = |
---|
121 | s.num e.res; |
---|
122 | |
---|
123 | /* |
---|
124 | * Add to the first list all new elements from the second one. |
---|
125 | */ |
---|
126 | Or (e.list1) e.list2 = |
---|
127 | (e.list1) e.list2 $iter { |
---|
128 | e.list2 : term e.rest, |
---|
129 | { |
---|
130 | e.list1 : e term e = (e.list1) e.rest; |
---|
131 | (e.list1 term) e.rest; |
---|
132 | }; |
---|
133 | } :: (e.list1) e.list2, |
---|
134 | e.list2 : /*empty*/ = |
---|
135 | e.list1; |
---|
136 | |
---|
137 | /* |
---|
138 | * Choose from the first list all elements present in the second one. |
---|
139 | */ |
---|
140 | And (e.list1) e.list2 = |
---|
141 | (e.list1) /*empty*/ $iter { |
---|
142 | e.list1 : term e.rest, |
---|
143 | { |
---|
144 | e.list2 : e term e = (e.rest) e.and term; |
---|
145 | (e.rest) e.and; |
---|
146 | }; |
---|
147 | } :: (e.list1) e.and, |
---|
148 | e.list1 : /*empty*/ = |
---|
149 | e.and; |
---|
150 | |
---|
151 | /* |
---|
152 | * Choose from the first list all elements not present in the second one. |
---|
153 | */ |
---|
154 | Sub (e.list1) e.list2 = |
---|
155 | (e.list1) /*empty*/ $iter { |
---|
156 | e.list1 : term e.rest, |
---|
157 | { |
---|
158 | e.list2 : e term e = (e.rest) e.not; |
---|
159 | (e.rest) e.not term; |
---|
160 | }; |
---|
161 | } :: (e.list1) e.not, |
---|
162 | e.list1 : /*empty*/ = |
---|
163 | e.not; |
---|
164 | |
---|